Eco-Dyeing of Timor Woven Fabrics using Pterocarpus Indicus Bark Tannin as a Natural Mordant - Adu, Risna Erni Yati; Fay, Angela Desy Putry; Tea, Marselina Theresia Djue (Hydrogen: Jurnal Kependidikan Kimia, 2024)
Pterocarpus indicus is a tropical wood type containing tannin compounds which potentially to be used as biomordants in woven fabrics dyeing. This research is the first work to determine the color cha racteristics of Timorese woven fabric after using tannin from Pterocarpus indicus bark as a biomordant. This research aims to determine the tannin content and colour properties of Timor woven fabric after using tannin as a a natural mordant. Pterocarpus indicus bark samples were prepared and extracted via hot extraction. The tannins in Pterocarpus indicus stem bark were qualitatively and quantitatively analyzed using FT-IR and UV-Vis Spectrophotometer respectively, then applied as a color binder for woven threads. The color properties of woven fabrics with tannin were compared to woven fabrics treated with Al2(SO4)3 mordant at a concentration of 15%. Color fastness to washing are tested using the Staining Scale Standard. Pterocarpus indicus bark tannin is a brown powder. Qualitative and quantitative tests show that Pterocarpus indicus bark contains tannins with a total concentration of 0.0436%. FTIR spectra exhibited functional groups absorption by the aromatic C-H, O-H, C=C, C-C, C-O-C, and C-O. The use of 15% tannin and curcumin dye produces a yellow-brown woven fabric with a fairly good color fastness value to washing. Pterocarpus indicus bark contains tannin which has potential as a biomordant for natural Timorese weaving dyeing.